Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the 2021 ACM Conference on Fairness, Accountability, and Transparency 2021
DOI: 10.1145/3442188.3445886
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Misuse of Counterfactuals in Ethical Machine Learning

Abstract: The use of counterfactuals for considerations of algorithmic fairness and explainability is gaining prominence within the machine learning community and industry. This paper argues for more caution with the use of counterfactuals when the facts to be considered are social categories such as race or gender. We review a broad body of papers from philosophy and social sciences on social ontology and the semantics of counterfactuals, and we conclude that the counterfactual approach in machine learning fairness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 39 publications
0
49
0
Order By: Relevance
“…Unfortunately, this fairness metric also comes with some difficulties in analyzing and evaluating the counterfactual statements. See Kasirzadeh and Smart [26] for some principled arguments against the prevalent use of counterfactual fairness in social contexts.…”
Section: Interpreting the Fairness Principle In Light Of Fairness Metricsmentioning
confidence: 99%
“…Unfortunately, this fairness metric also comes with some difficulties in analyzing and evaluating the counterfactual statements. See Kasirzadeh and Smart [26] for some principled arguments against the prevalent use of counterfactual fairness in social contexts.…”
Section: Interpreting the Fairness Principle In Light Of Fairness Metricsmentioning
confidence: 99%
“…There are also concerns about considering categories such as race or gender as a cause [30,26,15,22]. From one perspective, most of these attributes are determined at the time of an individual's conception and are modeled as source nodes in a causal graph which can directly or indirectly influence the descendent variables.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, many view attributes such as race or gender as social constructs that evolve over the course an individual's life. Recently, [15,22] studied epistemological and ontological aspects of counterfactuals in the context of fairness evaluation. In [15], the authors argue that social categories such as race may not admit counterfactual manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…One suggested solution to address the issue of spurious features is counterfactually augmented data (CAD)-instances generated by human annotators that are minimally edited to flip their labeland their variations such as iterative benchmark design (Potts et al, 2020), contrast data generation (Gardner et al, 2020), 1 and their combination . Drawing on the rich history of counterfactuals (Pearl, 2018;Lewis, 2013;Kasirzadeh and Smart, 2021), the promise of CAD is to offer a causality-based framework where only cues that are meaningfully associated with the construct are edited -which is expected to be conducive to models learning less spurious features. Indeed, recent work has shown that models trained on CAD generalize better out of domain (Kaushik et al, 2020;Samory et al, 2021).…”
Section: Introductionmentioning
confidence: 99%